Erstlinientherapie des behandlungsbedürftigen Multiplen Myeloms: Aktuelle Empfehlungen - John, Lukas; Goldschmidt, Hartmut; Scheid, Christoph (Deutsche medizinische Wochenschrift, 2020)
Due to the introduction of novel therapeutic agents, the prognosis of Multiple Myeloma has greatly improved over the last decades. The current standard for fit patients is a bortezomib-based induction therapy, followed by high-dose chemotherapy and autologous stem cell transplantation and lenalidomide-based maintenance therapy. For older, non-transplant-eligible patients, daratumumab in combination with bortezomib or lenalidomide offers a well-tolerated, effective treatment option. Despite large improvements, there is still no cure for most myeloma patients, the aim of therapy is therefore to reach a deep remission to prevent lasting damage followed by a continuous maintenance therapy to uphold the remission and prolong overall survival.
Gesehen am 02.06.2021